1986
DOI: 10.1080/10426918608953175
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Simulation Op Internal Void Closure in Open-Die Press Forging

Abstract: In the manufacturing of heavy forgings, one of the most important aspects of the process is the consolidation of internal voids which result from the ingotmaking process. To insure a good quality finished product. these voids must be closed by proper choice of forging practices -including such factors as die geometry, amount of reduction, reduction speed. and workpiece temperature. This paper focuses on the first two of these factors and reports the results of a study on the effects of die width and reduction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 7 publications
0
8
0
1
Order By: Relevance
“…As per [12], the effective strain was a better indicator of void closure than the hydrostatic stress. Shah et al [13] showed that voids could be closed by proper choice of forging practices including such factors such as die geometry, amount of reduction, reduction speed, and workpiece temperature. Kiuchi and Hsiang [14] discussed analytically the behavior of internal porosity in a plate rolling process using the method of limit analysis.…”
Section: Casting Defects/voids and Their Closuresmentioning
confidence: 99%
“…As per [12], the effective strain was a better indicator of void closure than the hydrostatic stress. Shah et al [13] showed that voids could be closed by proper choice of forging practices including such factors such as die geometry, amount of reduction, reduction speed, and workpiece temperature. Kiuchi and Hsiang [14] discussed analytically the behavior of internal porosity in a plate rolling process using the method of limit analysis.…”
Section: Casting Defects/voids and Their Closuresmentioning
confidence: 99%
“…Shah [7] e Wolske [8] Spur [9], analisou a mudança do avanço da ferramenta, alterando de uma mordida inicial com grande superfície de contato entre a ferramenta e a peça, Figura 4, em A, para mordidas posteriores mais curtas em B da figura 4. A segunda seção da peça, junto ao ponto central do eixo X, evidencia a falta de deformação no núcleo da peça (cor cinza escuro).…”
Section: Figuraunclassified
“…In spite of its significance, the related research works are not sufficient enough to be a guide for process design engineers. The reason lies in that both experimental approaches [1][2][3][4] and analytical or numerical approaches [5][6][7][8][9][10][11][12][13][14] have their own limitations. That is, experiments of large-scaled materials are very costly and difficult and most conventional simulation techniques are also poor at describing the pore closing phenomena due to their poor remeshing capability.…”
Section: Introductionmentioning
confidence: 99%
“…Stahlberg et al 6 studied rectangular cavity closing by the upper-bound method and they compared the predictions with experiments. From the late 1980s, finite element methods [7][8][9][10][11][12][13][14] have been used to study the pore closing phenomena in open die forging. Shah et al 7 applied threedimensional rigid-plastic finite element method to simulating open die forging processes without considering the pore closing phenomena.…”
Section: Introductionmentioning
confidence: 99%